Model pembelajaran PJOK berbasis Green School untuk meningkatkan kesadaran ekologis dan aktivitas fisik siswa MI Arohmat Sumberingin - Nur Ridwan Fauzen; Akbar Rohmad Aulia; Valentino Hery M (Patria Educational Journal (PEJ), 2025)
The integration of Physical Education, Sports, and Health (PJOK) learning with environmental education at the elementary school level, especially in Islamic elementary schools, is still limited. PJOK learning generally still focuses on improving motor skills without strengthening ecological values, whereas the issue of environmental degradation and low physical activity of school-age children demands more contextual and sustainable learning innovations. Therefore, a learning model is needed that is able to combine physical activity with ecological awareness in an integrated manner. This study uses a Research and Development (R&D) approach with stages including needs analysis, model design, product development, expert validation, limited trials, and field trials. Data were collected through observation, interviews, questionnaires, and physical activity and ecological awareness tests, then analyzed quantitatively and qualitatively to see the effectiveness of the developed model. The results of the study indicate that the Green School-based PJOK learning model at MI Arohmat Sumberingin is effective in increasing ecological awareness and physical activity of students. The integration of the school environment as a learning resource creates more active, contextual, and meaningful learning. Students demonstrated increased environmental awareness, participation in nature-based activities, and optimal movement intensity during learning. Thus, this model not only improves physical fitness but also fosters environmental stewardship and sustainable healthy lifestyle habits in elementary schools.